Hubungan Tingkat Pengetahuan dan Sikap Perawat Tentang Infeksi Nosokomial (INOS) Dengan Perilaku Pencegahan INOS Di Ruang Bedah RSUD DR. Moewardi Surakarta - Dwi Sulistyowati ((JKG) Jurnal Keperawatan Global, 2016)
Abstract: Knowledge, Attitudes, Behaviors, Inos, Nurse. Nosocomial infections (inos) is an infection acquired during patient care in hospitals, infection is not in pain at the time of hospital admission and the patient is not within an incubation period of infectious diseases. The study aims to determine the relationship between the level of knowledge and attitudes to the behavior of nurses regarding the prevention of inos in the operating room of RSUD Dr. Moewardi Surakarta. Design used in this study was descriptive correlational cross-sectional approach. Sampling was carried out with total non-probability sampling, sample size of 30 respondents. There is a relationship between the level of the nurse’s knowledge about preventive behaviors inos with a probalility value of Spearman’s Rank correlation test for p = 0,024 is smaller than the probability p = 0,05. There is no relationship between nurse attitudes about preventive behaviors inos with a probability value of Spearman's Rank correlation test for p = 0.759 greater than the probability p = 0.05. There is a relationship between the nurse's knowledge about preventive behavior with inos. There is no relationship between attitudes to the behavior of nurses regarding the prevention of inos.